Trade liberalization and the hukou system of the People's Republic of China: How migration frictions can amplify the unequal gains from trade - Yuan Zi (Asian Development Bank Institute (ADBI), 2018)
The emergence of the People's Republic of China (PRC) as a great economic power has stimulated an epochal shift in patterns of world trade, accompanied by a remarkable level of internal migration within the country. Hundreds of millions of Chinese workers have moved from inland areas to coastal cities, contributing to the PRC's manufacturing growth and export surges. However, alongside this significant reallocation in labor and increased economic growth, the redistribution of the gains from trade has been extremely limited due to the PRC's household registration system (hukou). By prohibiting migrant workers from accessing various social benefits in their actual cities of residence, urban areas experiencing positive trade shocks may receive smaller migration inflows. At the worker level, a larger proportion of the gains accrues to workers holding local hukou, and hence the uneven regional gains from trade are translated to uneven gains across people holding different types of hukou. At the national level, the hukou system has prevented the country from achieving the optimal spatial adjustments of labor to trade shocks.
Keywords: F11; F13; F16; R23; O15; 330; trade liberalization; spatial labor reallocation; hukou frictions; migration